Hubungan di antara motivasi, persekitaran kerja, kerja berpasukan dan kepimpinan terhadap kepuasan kerja: Kajian di kalangan staf Uniutama Property Sdn. Bhd. - Siti Shuhaila, Mohd Nor (2018)
Uniutama Property Sdn Bhd (UPSB) is expected to be one of the largest contributors to employment opportunities for residents around Universiti Utara Malaysia. UPSB should always ensure job satisfaction among its employees in order to produce quality work and increase productivity of the company. Therefore, organizations need to identify the factors of job satisfaction among employees who can influence their level of job satisfaction. The purpose of this study is to examine the relationship between motivation, work environment, teamwork and leadership towards employee satisfaction among UPSB employees. Simple random sampling technique was used to carry out the study of 144 respondents using questionnaires. Based on pearson correlation analysis, there is a relationship between motivation, work environment, teamwork and leadership with job satisfaction. Impact, motivational and leadership elements need to be taken into account in the management of companies where employees are confident of their ability to succeed at work and the leader plays an important role in listening to work-related problems. In conclusion, motivation is the biggest contributor to job satisfaction among UPSB workers, UUM Inasis.